The accidental highwayman : being the tale of Kit Bristol, his horse Midnight, a mysterious princess, and sundry magical persons besides - Tripp, Ben, 1966- (New York : Tom Doherty Associates, 2014)
In eighteenth-century England, young Christopher "Kit" Bristol unwittingly takes on the task of his dead master, notorious highwayman Whistling Jack, who pledged a fairy he would rescue feisty Princess Morgana from an arranged marriage with King George III.
English Language & Literature.
Keywords: Robbers and outlaws -- Fiction; Adventure and adventurers -- Fiction; Fairies -- Fiction; Magic -- Fiction; Princesses -- Fiction; Fate and fatalism -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General; Great Britain -- History -- George III, 1760-1820 -- Fiction